Explorative Mediation at Work The Importance of Dialogue for Mediation Practice - Seaman, Roger; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Exploring and critiquing various methods of mediation, this innovative book critically develops a new explorative practice in the field. Considering ways in which mediators may influence disputing parties, especially in the workplace where mediators are paid to intervene, Explorative Mediation at Work questions the common claim that mediation is a neutral intervention. The difference between offering minimally intrusive support and acting to secure a containment and even suppression of workplace conflict is heavily dependent upon a mediator$1 (Bs practices. At worst, engineering resolution may tarnish mediation$1 (Bs reputation for impartiality. At best, mediation can win the trust of parties in conflict, facilitate a democratic engagement and be of real benefit to organizations. This book aims to demonstrate the latter in proposing a practice that supports parties to seek out dialogue from which relationships may be rebuilt and practical problems resolved.s
Chapter 1 Introduction -- Chapter 2 A spectrum of mediator influence -- Chapter 3 Mediation in the workplace -- Chapter 4 Political awareness and dialogue -- Chapter 5 Instrumental mediation -- Chapter 6 Relational mediation -- Chapter 7 Explorative mediation: An instrumental, ethical and political approach -- Chapter 8 Conclusion -- References -- Index.
Keywords: Business; Organization; Planning; Manpower policy; Social responsibility of business; Mediation; Dispute resolution (Law).; Conflict management; Business and Management; Human Resource Development; Corporate Social Responsibility; Organization; Dispute Resolution, Mediation, Arbitration; Electronic books